Digital Gamification in Legal Education: Enhancing Academic Engagement and Professional Competencies. - Кіріяк, Оксана Василівна (Одеса, Видавництво ОНТУ, 2026 р., 2026)
The rapid digitalization of higher education has transformed traditional pedagogical approaches, particularly in professional fields such as legal education. Gamification – defined as the use of game design elements in non-game contexts – has emerged as an innovative method to enhance student engagement, motivation, and learning outcomes. This paper explores the role of digital gamification in legal education, focusing on its impact on academic performance, student participation, and the development of professional competencies. Drawing on contemporary research and practical applications, the study highlights both opportunities and challenges associated with integrating gamified learning into legal curricula. Special attention is given to the role of gamification in fostering language proficiency and supporting international academic collaboration.
Keywords: Legal Education, Digitalization, E-learning, Remote Format, Gamification of Education